2019
DOI: 10.1159/000502405
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A for the Prevention of Ocular Graft versus Host Disease in Allogeneic Hematopoietic Stem Cell Transplant Recipients Is Safe and Feasible

Abstract: To evaluate the safety and efficacy of ocular cyclosporine in the prevention of the development of ocular graft versus host disease (oGVHD) in patients undergoing allogeneic hematopoietic stem cell transplantation (AHSCT) in comparison with historic data. Design: We developed a longitudinal, observational, prospective nonrandomized study. We evaluated the feasibility of prophylactic use of topical cyclosporine A (CsA) to prevent or decrease the incidence of oGVHD and compared this with historic data. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Several case studies have reported successful treatment using oral cyclosporine for ocular surface inflammatory disorders including limbal stem cell deficiency (LSCD), necrotizing scleritis, severe keratoconjunctivitis, and corneal graft rejection 37 41 . Several studies have reported that the initiation of topical cyclosporine in the pre-transplantation phase could reduce the inflammatory response in the lacrimal glands that may be responsible for the development of keratitis sicca 35 , 42 . They proposed that topical cyclosporine treatment in the early phase could achieve greater tissue levels of CsA and possibly forestall inflammatory damage to the lacrimal acini in GVHD 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies have reported successful treatment using oral cyclosporine for ocular surface inflammatory disorders including limbal stem cell deficiency (LSCD), necrotizing scleritis, severe keratoconjunctivitis, and corneal graft rejection 37 41 . Several studies have reported that the initiation of topical cyclosporine in the pre-transplantation phase could reduce the inflammatory response in the lacrimal glands that may be responsible for the development of keratitis sicca 35 , 42 . They proposed that topical cyclosporine treatment in the early phase could achieve greater tissue levels of CsA and possibly forestall inflammatory damage to the lacrimal acini in GVHD 35 .…”
Section: Discussionmentioning
confidence: 99%
“…oGVHD can be prevented with the use of topical cyclosporine. Cantú-Rodríguez et al 21 reported a decrease in oGVHD cases due to the immunosuppressive properties of cyclosporine, demonstrating its effectiveness as prophylaxis for oGVHD to prevent ocular damage.…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, it was directly effective in improving aqueous tear production, reducing GVHD-ocular surface inflammation, and increasing cell density 27 . Moreover, CsA has been demonstrated to be a feasible prophylactic measure for oGVHD 21 . Dietrich-Ntoukas et al 16 reported the effectiveness of topical CsA when steroids did not work.…”
Section: Immunoregulatorsmentioning
confidence: 99%
“…(Dietrich‐Ntoukas et al, 2012) A recent paper showed that topical CsA treatment after HSCT was effective in preventing the onset of ocular complications of GVHD, during a period of 1 year of follow‐up. (Cantu‐Rodriguez et al, 2020) Topical CsA showed also to be effective in controlling ocular inflammation management when steroid does not work (Dietrich‐Ntoukas et al, 2012). Specifically, few case series and two CRT showed the improvement of tear function and ocular signs in moderate to severe dry eye related to cGVHD (Lelli et al, 2006; Sall et al, 2000; Wang et al, 2008).…”
Section: Management and Treatmentmentioning
confidence: 99%